2014
DOI: 10.1155/2014/803219
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Corrosive Bacterial Consortia Isolated from Water in a Cooling Tower

Abstract: An analysis of a culturable corrosive bacterial community in water samples from a cooling tower was performed using traditional cultivation techniques and its identification based on 16S rRNA gene sequence. Seven aerobic bacterial species were identified: Pseudomonas putida ARTYP1, Pseudomonas aeruginosa ARTYP2, Massilia timonae ARTYP3, Massilia albidiflava ARTYP4, Pseudomonas mosselii ARTYP5, Massilia sp. ARTYP6, and Pseudomonas sp. ARTYP7. Although some of these species have commonly been observed and report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Two different sizes of metal coupons were used in the present investigation: a round coupon with diameter of 10 mm for EIS analysis and a 7.5 cm × 1 cm × 0.1 cm coupon for the weight loss experiment. 41…”
Section: Methodsmentioning
confidence: 99%
“…Two different sizes of metal coupons were used in the present investigation: a round coupon with diameter of 10 mm for EIS analysis and a 7.5 cm × 1 cm × 0.1 cm coupon for the weight loss experiment. 41…”
Section: Methodsmentioning
confidence: 99%
“…According to Aruliah and Ting (2014), twelve 250 mL conical flasks were prepared. Each flask contains a 100 mL sterile test water sample which was previously sterilized by autoclaving and inserted three peace of prepared coupons.…”
Section: Weight Loss Methodsmentioning
confidence: 99%
“…Microbiologically Influenced Corrosion (MIC) is directly related to the presence and adherence of the microbes on industrial pipes subsequent metal deterioration and damage as a result of microbial activities that modify local chemistry at metal surfaces caused biocorrosion (Gu et al, 2019). Biofilm extracellular polysaccharide substance has sticky properties that aid the adherence to metal surfaces and protect bacterial elimination by biocides subsequently causing corrosion (Aruliah and Ting, 2014). The mixed culture biofilm type showed synergistic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ISO has a strong inhibitor efficacy on the growth of SRB not only in cooling towers but also in oilfield injection, paper-mill and metalworking fluid systems [12][13][14]. Aruliah et al (2014) reported significantly less pitting corrosion on the surfaces of copper in the presence of the bronopol [15]. It has also been reported that, while glutaraldehyde (GD) is very effective on SRB on carbon steel surfaces, inhibiting localized corrosion significantly, azole is particularly effective on SRB on copper alloys [16].…”
Section: Introductionmentioning
confidence: 99%